Low voltage operation of electro-absorption modulator promising for high-definition 3D imaging application using a three step asymmetric coupled quantum well structure. (21st January 2015) - Na, Byung Hoon; Ju, Gun Wu; Choi, Hee Ju; Lee, Soo Kyung; Jeon, Jin Myeong; Cho, Yong Chul; Park, Yong Hwa; Park, Chang Young; Lee, Yong Tak
Abstract: In this paper, we propose a transmission type electro-absorption modulator (EAM) operating at 850 nm having low operating voltage and high absorption change with low insertion loss using a novel three step asymmetric coupled quantum well (3 ACQW) structure which can be used as an optical image shutter for high-definition (HD) three dimensional (3D) imaging. Theoretical calculations show that the exciton red shift of 3 ACQW structure is more than two times larger than that of rectangular quantum well (RQW) structure while maintaining high absorption change. The EAM having coupled cavities with 3 ACQW structure shows a wide spectral bandwidth and high amplitude modulation at a bias voltage of only -8V, which is 41% lower in operating voltage than that of RQW, making the proposed EAM highly attractive as an optical image shutter for HD 3D imaging applications.